Academicians Satisfy of The Faculty of Economics, in Universitas Negeri Surabaya Throught on Total Quality Management - Susi Handayani; Pujiono Pujiono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The Faculty of Economics in Universitas Negeri Surabaya had certified of International standard operating (ISO) for quality management since 2015. This certification prosecutes management of faculty of economics to increase service quality to academicians. The important aspects of ISO have to determine TQM implemented. Therefore, it had created quality assurance team that exist gradually at university to study program. A service quality must be guarantied by internal and external audit. However, it improves continuous improvement that based on audit results, especially low students satisfaction, officer alacrity to give a service, ability to explanation, handling of complaints, courtesy and friendliness, and support infrastructures for learning process. All cost of quality assurance conduct to prepare an audit internal implementation, to up-date accreditation forms and performance of study program, and monitoring and evaluation for learning and curriculum, improve a quality procedure, prepare and evaluation a quality target, and follow up on audit finding.Keywords: ISO, service quality, student satisfaction, total quality management